Suppression of intestinal carcinogenesis in Apc-mutant mice by limonin - Shimizu, Satomi; Fujimoto, Kyoko; Mutoh, Michihiro; Ozaki, Yoshihiko; Yano, Tomohiro; Nakanishi, Ruri; Onuma, Wakana; Fujii, Gen; Miyamoto, Shingo (Journal of Clinical Biochemistry and Nutrition, 2015)
Limonoids in citrus fruits are known to possess multiple biological functions, such as anti-proliferative functions in human cancer cell lines. Therefore, we aimed to investigate the suppressive effect of limonin on intestinal polyp development in Apc-mutant Min mice. Five-week-old female Min mice were fed a basal diet or a diet containing 250 or 500 ppm limonin for 8 weeks. The total number of polyps in mice treated with 500 ppm limonin decreased to 74% of the untreated control value. Neoplastic cell proliferation in the polyp parts was assessed by counting PCNA positive cells, and a tendency of reduction was obtained by limonin treatment. Moreover, expression levels of c-Myc and MCP-1 mRNA in the polyp part were reduced by administration of limonin. We finally confirmed the effects of limonin on β-catenin signaling, and found limonin significantly inhibited T-cell factor/lymphocyte enhancer factor-dependent transcriptional activity in a dose-dependent manner in the Caco-2 human colon cancer cell line. Our results suggest that limonin might be a candidate chemopreventive agent against intestinal carcinogenesis.